Maternal supplementation with selenium nanoparticles enhances reproductive outcomes and larval quality in Asian seabass (Lates calcarifer) by influencing gene expression and physiological parameters - Seyed Ali Khorasaninasab; Saeed Keyvanshokooh; Mansour Torfi Mozanzadeh; Ahmad Ghasemi; Mahdi Naderi; Samira Nazemroaya (Aquaculture Reports)
Selenium plays vital roles in antioxidant defense, immune function, and reproductive physiology in vertebrates. This study evaluated the impacts of dietary selenium nanoparticles (SeNPs) on reproductive outcomes, steroidogenesis, vitellogenesis, and larval quality in female Asian seabass (Lates calcarifer), by influencing gene expression, antioxidant capacity, hormone levels, and reproductive indices. Female broodfish (n = 12; 1990 ± 120 g) were fed either a basal diet (control) or a basal diet supplemented with 2 mg SeNPs/kg (SeNPs-2) for 120 days before spawning. Supplementation with SeNPs significantly (P < 0.05) increased Se deposition in the liver, ovary, and larvae, enhancing antioxidant capacity (glutathione peroxidase and reduced-glutathione), and reducing oxidative stress marker (malondialdehyde; MDA) in both broodfish and offspring. The expression levels of genes involved in steroidogenesis (star, P450scc, and 3β-hsd) and vitellogenesis (zp2 and vtg) were upregulated in the ovary or liver of the SeNPs-2 group (P < 0.05). Despite comparable serum testosterone and estradiol levels (P > 0.05), broodfish fed the SeNPs-2 diet exhibited significantly (P < 0.05) lower progesterone levels, and lower serum cholesterol and triglyceride levels. Reproductive performance, as indicated by spawning frequency, relative fecundity, fertilization rate, and hatching rate, was significantly (P < 0.05) improved in the SeNPs-2 group. Larvae descending from the SeNPs-fed broodfish exhibited higher expression of growth-promoting genes (GH and IGF-I), larger body size, and better developmental traits than those from the control group. These findings suggest that dietary SeNP supplementation positively influences Se bioavailability, gene expression, reproductive efficiency, and larval quality in L. calcarifer. SeNPs represent a promising nutritional strategy for optimizing broodstock performance and enhancing offspring quality in aquaculture.